Implementasi Program Corporate Social Responsibility (CSR) PT Pertamina (Persero) Fuel Terminal Medan Group Dalam Pemberdayaan Masyarakat Ecobrick Pada Kelompok Mawar Berduri - Hanafi Ahmar; Nurul Azmi; Ayu Restianti (UIN Siber Syekh Nurjati Cirebon, 2021)
The trash problem in Indonesia is endless. Garbage is still the main problem in Indonesia, including in Environment 24, Pekan Labuhan, Medan City, North Sumatra. The CSR of PT Pertamina (Persero) Medan Group Fuel Terminal is present as a form of corporate responsibility in overcoming trash problems in communities who live around the company with an ecobrick empowerment program. This study will look at the implementation of the PT Pertamina (Persero) Medan Group's Corporate Social Responsibility (CSR) program in the empowerment of the ecobrick community in the Mawar Berduri Group. This research uses a qualitative approach. The object of this research study is the CSR of PT Pertamina (Persero) Medan Group Fuel Terminal and Mawar Berduri Group. Implementers, companies, and the Mawar Berduri Group were the sources of research data. Other data sources were taken from the activity document archives, observations, interviews, and documentation. The results showed that the implementation of the PT Pertamina (Persero) Medan Group Fuel Terminal's Corporate Social Responsibility (CSR) program in empowering the ecobrick community in the Mawar Berduri Group had gone well and fulfilled all four indicators including communication, resources, disposition, and bureaucratic structure. Although based on the results of observations in the 2020 IKM, the downstream pattern of inputs, outputs and outcomes of the Ecobrick program still does not look optimal. This is indicated by the ecobrick marketing pattern that has been carried out and the level of ecobrick income that is still relatively low for the group category.